Representas Diskriminasi Perempuan Jawa Dalam Series Gadis Kretek (Analisis Semiotika Roland Barthes) - Yahya, Nur Alifah Z.; Talani, Noval Sufriyanto; Juniarti, Gita (Jambura Jurnal Ilmu Komunikasi, 2025)
This stydy analyzes the representation of discrimination against the Javanese female character, Dasiyah , in the Gadis Kretek series. What distinguishes this study from others is its focus on discrimination, specifically experienced by Dasiyah as a Javanese woman involved in the kretek (clove cigarette) industry. The primary focus is on how gender-based discrimination is portrayed, particularly toward women parcitipating in the kretek business. The objectives of this research are to describe the signs of discrimination against Javanese women as portrayed through the character Dasiyah, and to analyzes the meanings and myths associated with the image of the “Javanese girl” as represented in the series. This research employs a qualitative approach using Roland Barthes’ semiotic method to uncover the denotative, connotative, and mythological meanings embedded in discriminatory scenes. The findings reveal the restriction of women ‘s roles, negative labeling of women active in public spaces, and the silencing of women’s voices within business inheritance systems. Dasiyah is represented as a figure of resistance to the myth of the Javanese woman through three core Javanese cultural values: Rukun (harmony), Sabar (patience), and Nrimo ing pandum (grateful acceptance). The series serves as a medium of critique against patriarchal culture and traditional gender constructs in Javanese community